Turismo Religioso en la provincia de Cotopaxi: caso de estudio Fiesta en honor al Dr. San Buenaventura, parroquia San Buenaventura, cantón Latacunga. - Iza Iza, Katherine Adela (2022)
The current research work was carried out in the San Buenaventura parish, Latacunga city, Cotopaxi province, which it has as aim to study religious tourism, through the celebration in honor of Dr. San Buenaventura. The research has a non-experimental qualitative methodological approach, since it will be collected data, in order to know the cultural and traditional features of said celebration. For the first aim, it was applied the ethnographic methodology to describe and interpret the manifestation, with the techniques help, such as semi-structured interviews (key questions), what allowed greater rapprochement and a dialogue environment between the interviewee and the interviewer. The same way, it was handled the methodology from Cultural Heritage National Institute, through the inventory sheets as an instrument, which helps the adequate information collected systematization. Getting as a result, the 3 material assets identification, separated by furniture 2 pieces, which are clothing or saint clothing of saint and sculpture of saint, while by property was identified the San Buenaventura Catholic Church. In the intangible heritage case was identified 9 heritages separated by areas, which Area 1. Traditions and oral expressions, oral expressions sub-area identified: praises, songs, prayers, and legends related to Buenaventura; Area 3. Social uses, rituals and festive acts, religious ceremonies sub- area was identified festivities in honor to Dr. San Buenaventura, in the same way, in the cult and transition rites sub-area: command change; Area 4 Knowledge and uses related to nature and the universe, gastronomic sub-area colada morada, fritada, traditional bread in a wood-fired oven. The second aim, it was applied the inductive method, since it allowed to collect data, directly, with the survey technique help, through the questionnaire instrument, which it will facilitate getting the necessary information for the research, in conjunction with the analytical method for the data analysis and interpretation the got results in the survey application to tourists and visitors, who attended the celebration. Which it was determined, what it is an internal tourism, due to 96,43% are Ecuadorians, the same way 56,4 % are Latacunga residents. Their travel form is mainly with the family and they spend a 20 dollars average. As for the third aim, it was applied the synthetic method, because it helped generate an analysis, through this presents the research results in a summarized way as a proposal for an academic article. This is based on the scientific journal Pasos (Tourism and Cultural Heritage magazine) structure, which has as aim to disseminate articles on the different processes, what it encompasses the tourism system.